2014
DOI: 10.5901/mjss.2014.v5n13p177
|View full text |Cite
|
Sign up to set email alerts
|

How to Facilitate Implementation of Lean Concept?

Abstract: The paper reveals to the challenges and barriers to be faced and overcomed while implementing lean concept. Lean manufacturing, lean enterprise, or simply "Lean", is a practice, which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…The findings also revealed that TQM and partnering have a strong and positive correlation between all the environmental attributes performance. The performances are reducing construction wastes, compliance with local authority's or government requirement, reducing the energy consumption of the project and producing a neat and clean site environment [13][14][15][16]. The findings proved a research by Caldera et al [12] that the implementation of LC can improve the contractor's environmental performance…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The findings also revealed that TQM and partnering have a strong and positive correlation between all the environmental attributes performance. The performances are reducing construction wastes, compliance with local authority's or government requirement, reducing the energy consumption of the project and producing a neat and clean site environment [13][14][15][16]. The findings proved a research by Caldera et al [12] that the implementation of LC can improve the contractor's environmental performance…”
Section: Resultsmentioning
confidence: 87%
“…According to Caldera et al [12], the implementation of LC can improve the environmental performance of a construction project. Previously, in placing more emphasis, Ciarniene and Vienazindiene [13] stated that the implementation of LC tools will reduce the construction wastes at the site as per Table 2. The similar research area also mentioned a project will comply with a local authority or government requirement [14] and reduce the energy consumption of a project [15].…”
Section: Lean Construction Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Economic dimension -long-time implementation, misallocation of resources, administrative cost (Čiarnienė and Vienažindienė, 2014). • Environmental dimension -waste disposal, pollution, trade-offs with operational performance (Resta et al, 2017).…”
Section: Lean Manufacturingmentioning
confidence: 99%
“…• Environmental dimension -waste disposal, pollution, trade-offs with operational performance (Resta et al, 2017). • Social dimension -routine operation, employee mistrust, trade-offs with operational performance (Čiarnienė and Vienažindienė, 2014;Resta et al, 2017).…”
Section: Lean Manufacturingmentioning
confidence: 99%